Primary small-cell carcinoma of the trachea - Uncommon but aggressive (Indian Journal of Case Reports, 2025)
Primary tracheal tumors are rare, and small-cell carcinoma (SCC) of the trachea is an extremely rare and aggressive cancer. Treatment guidelines for tracheal SCC are not available because it is not common. Only a few cases have been reported in the literature to date. We describe the case of a 60-year-old man with a persistent cough. Biopsy and immunohistochemistry tests showed primary tracheal SCC. On imaging, it was confirmed as localized and did not have any distant metastases. The patient received neoadjuvant chemotherapy followed by chemoradiation and maintenance chemotherapy. Even though he responded well at first, he got skeletal metastases within 6 months. Individual case reports and retrospective research contribute to existing treatment options, which include surgical resection, chemoradiation, and chemotherapy alone. Small-cell lung cancer management methods are often used to guide treatment. Care standards need to be improved with the help of more research.